Validation of Academic Resilience Scales Adapted in a Collective Culture - Cui, Tianxue; Wang, Chuang; Xu, Jianzhong (Frontiers in Psychology, 2023)
The study aimed to adapt and validate two popular instruments on academic resilience in a collectivistic culture. One is a brief unidimensional scale (ARS_SCV), and another is a context-specific multidimensional scale (ARS_MCV). Based on the data from 569 high school students in China, results indicated that both scales were reliable with high internal consistency and construct reliability. Based on Messick’s (1989a) validity framework, we provided evidence to support the construct validity of the newly developed scales. Results of confirmation factor analyses (CFAs) showed that ARS_SCV had a unidimensional factor structure and ARS_MCV had a four-factor structure. Multi-group CFAs then showed that both models were invariant across gender and socio-economic status (SES) levels. Results of correlations demonstrated that both scales significantly correlated with each other and with other external constructs (grit, academic self-efficacy, and learning engagement). Theoretical and practical implications are discussed.